2017
DOI: 10.1080/10408398.2016.1149690
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin cage for encapsulation and delivery of bioactive nutrients: From structure, property to applications

Abstract: Ferritin is a class of naturally occurring iron storage proteins, which is distributed widely in animal, plant, and bacteria. It usually consists of 24 subunits that form a hollow protein shell with high symmetry. One holoferritin molecule can store up to 4500 iron atom within its inner cavity, and it becomes apoferritin upon removal of iron from the cavity. Recently, scientists have subverted these nature functions and used reversibly self-assembled property of apoferritin cage controlled by pH for the encaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 85 publications
0
55
1
Order By: Relevance
“…The proportion of subunits varies between different organisms and between different tissues within an organism, reflecting the different functions, fast iron metabolism, or long-term iron storage required by different tissues [16,28]. In addition, for lower vertebrates, such as bullfrogs, fish, and tegillarca granosa, there is also an M (medium) subunit or H-like subunit containing both the ferroxidase center and the nucleation site in the ferritin of erythrocyte, and the three subunits can form heterozygous ferritin [25,29]. Differently, the mitochondria ferritin (MtF) found in human, mouse, and drosophila is a homopolymer with 24 identical subunits.…”
Section: Animal Ferritinmentioning
confidence: 99%
See 2 more Smart Citations
“…The proportion of subunits varies between different organisms and between different tissues within an organism, reflecting the different functions, fast iron metabolism, or long-term iron storage required by different tissues [16,28]. In addition, for lower vertebrates, such as bullfrogs, fish, and tegillarca granosa, there is also an M (medium) subunit or H-like subunit containing both the ferroxidase center and the nucleation site in the ferritin of erythrocyte, and the three subunits can form heterozygous ferritin [25,29]. Differently, the mitochondria ferritin (MtF) found in human, mouse, and drosophila is a homopolymer with 24 identical subunits.…”
Section: Animal Ferritinmentioning
confidence: 99%
“…As a nanocarrier for the encapsulation and delivery of nutrients and drugs, the digestive stability of ferritin in gastrointestinal tract has received wide attention from researchers. If ferritin cannot survive through gastrointestinal digestion, the prepared nanoparticles will make little contribution to human nutrition and or disease treatment through any absorption pathway [25]. However, a recent report has found that ferritin is not stable in the stomach, and most ferritin molecules can be degraded by pepsin at pH 2.0 in this region [129].…”
Section: Challenges Of Ferritin As a Nanocarriermentioning
confidence: 99%
See 1 more Smart Citation
“…The sizes of the casein particles were determined using a dynamic light scattering (DLS) instrument (Nano ZS, Malvern, UK) at 20 °C. The treated samples were diluted 500 times with water [ 37 ]. Separation of calcium in the soluble and micellar phases was carried out by ultracentrifugation at 80,000× g for 3 h at 20 °C (CP 80MX, Hitachi, Tokyo, Japan) [ 34 , 38 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…25 We have previously employed an ubiquitous protein, apoferritin (Apo), to be a potential carrier for Dox, with a simple-to-use encapsulation protocol (creating ApoDox). 29 Also, heavy-chain ferritin, 30 as well as other ferritins, have been used for delivery of anticancer drugs, 31 small nutrients, 32 and imaging molecules. 33 Subsequently, we modified the Apo surface with small molecules, 34 as well as antibodies for active targeting to cells of a chosen cancer type.…”
mentioning
confidence: 99%